Exendin-4 Exacerbates Burn-Induced Morbidity in Mice by Activation of the Sympathetic Nervous System - Xiao-Jing Ji; Ji-Wei Hao; Guang-Lei Li; Ning Dong; Xin-Qi Wang; Min Zhou; Qing-Hong Zhang; Yong-Ming Yao (Mediators of Inflammation)
Background. Although glucagon-like peptide 1- (GLP-1-) based therapy of hyperglycemia in burn injury has shown great potential in clinical trials, its safety is seldom evaluated. We hypothesize that exendin-4, a GLP-1 analogue, might affect the immune response via the activation of the sympathetic nervous system in burn injury. Methods. Male Balb/c mice were subjected to sham or thermal injury of 15% total body surface area. Exendin-4 on T cell function in vitro was examined in cultured splenocytes in the presence of β-adrenoceptor antagonist propranolol (1 nmol/L) or GLP-1R antagonist exendin (9-39) (1 μmol/L), whereas its in vivo effect was determined by i.p. injection of exendin-4 (2.4 nmol/kg) in mice. To further elucidate the sympathetic mechanism, propranolol (30 mg/kg) or vehicle was applied 30 min prior to injury. Results. Although the exacerbated burn-induced mortality by exendin-4 was worsened by propranolol pretreatment, the inhibition of T cell proliferation by exendin-4 in vitro could be restored by propranolol instead of exendin (9-39). However, a Th2 switch by exendin-4 in vitro could only be reversed by exendin (9-39). Likewise, the inhibition of splenic T cell function and NFAT activity by exendin-4 in vivo was restored by propranolol. By contrast, the increased splenic NF-κB translocation by exendin-4 in vivo was potentiated by propranolol in sham mice but suppressed in burn mice. Accordingly, propranolol abrogated the heightened inflammatory response in the lung and the accelerated organ injuries by exendin-4 in burn mice. On the contrary, a Th2 switch and higher serum levels of inflammatory mediators by exendin-4 were potentiated by propranolol in burn mice. Lastly, exendin-4 raised serum stress hormones which could be remarkably augmented by propranolol. Conclusions. Exendin-4 suppresses T cell function and promotes organ inflammation through the activation of the sympathetic nervous system, while elicits Th2 switch via GLP-1R in burn injury.